Validity of the Xiaomi Mi Band 2, 3, 4 and 5 Wristbands for Assessing Physical Activity in 12-to-18-Year-Old Adolescents under Unstructured Free-Living Conditions. Fit-Person Study. - Casado-Robles, Carolina; Mayorga-Vega, Daniel; Guijarro-Romero, Santiago; Viciana, Jesús (Journal of Sports Science & Medicine, 2023)
The purpose was to assess the validity of four generations of Xiaomi Mi Band wristbands for the assessment of step count and physical activity (PA) levels among adolescents aged 12- 18 years under free-living conditions. One hundred adolescents were invited to participate in the present study. The final sample consisted of 62 high-school students (34 females), aged 12 - 18 years old (Mage = 14.1 ± 1.6 years), who wore an ActiGraph accelerometer on their hip (PA and step count reference measures) and four activity wristbands (Xiaomi Mi Band 2, 3, 4, and 5) on their nondominant wrist during the waking time of one day. Results showed that the agreement between daily PA levels (i.e., slow, brisk, and slow-brisk pace walking, total PA and moderate-tovigorous PA) measured by Xiaomi Mi Band wristbands and the accelerometer were poor (ICC, 95% CI = 0.06 - 0.78, 0.00 - 0.92; MAPE = 50.1 - 150.6%). However, agreement between daily step count measured by the accelerometer and the Xiaomi Mi Band wristbands were between acceptable (MAPE = 12.2 - 13.6%) to excellent (ICC, 95% CI = 0.94 - 0.95, 0.90 - 0.97). Furthermore, the Xiaomi Mi Band wristbands have a good to excellent validity for correctly classifying adolescents as meeting or not meeting the recommended 10,000 steps per day (P = 0.89 - 0.95, k = 0.71 - 0.87) and the recommended 60 minutes of moderate-to-vigorous PA per day (P = 0.89 - 0.94, k = 0.69 - 0.83). Furthermore, comparability between the four Xiaomi Mi Band generations were poor to excellent (ICC, 95% CI = 0.22 - 0.99, 0.00 - 1.00) for the daily PA levels outputs, although it was excellent (ICC, 95% CI = 0.99 - 1.00, 0.96 - 1.00; MAPE = 0.0 - 0.1%) for daily step count. Different models of Xiaomi Mi Band wristbands were comparable and presented good validity for measuring adolescents' step count, and they accurately classified adolescents as meeting or not meeting the PA recommendations under free-living conditions.